2013
DOI: 10.1002/ajh.23488
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B‐cell compartment in transfused alloimmunized and non‐alloimmunized patients with sickle cell disease

Abstract: Transfusion therapy is a life-sustaining treatment for patients with sickle cell disease (SCD), but can cause serious complications including alloimmunization. We previously reported diminished regulatory T cells (Tregs) and skewed Th2 responses in alloimmunized SCD patients. We hypothesized that the B cell regulatory (Breg) compartment, which controls Treg and Th differentiation, may also be compromised in allosensitized SCD patients. Phenotypically, we did not find differences in the frequency or numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 34 publications
3
33
0
5
Order By: Relevance
“…Bao et al (2011) described differences in regulatory T cell (Tregs) subsets of SCD patients receiving regular blood transfusions with alloantibodies compared to those without, specifically a reduction in Treg activity, an increase toward T-helper cell type 2 (Th2) responses and lower serum levels of interleukin (IL) 10 in the alloimmunized group of patients. The same group (Bao et al, 2013) also presented data suggesting that regulatory B cells (Bregs) from alloimmunized and non-alloimmunized SCD patients differ in their ability to produce IL10 upon stimulation and dampen monocyte activation despite comparable frequencies of Bregs (CD19 + CD24 hi CD38 hi and CD24 hi CD27 + subsets) supporting an altered immunoregulatory state in alloimmunized SCD patients. Investigations of cytokine levels during acute SCD-related complications have shown increased neutrophil chemotaxis, monocyte phagocytosis and levels of IL6 and TNF during VOC (Graido-Gonzalez et al, 1998;Pathare et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Bao et al (2011) described differences in regulatory T cell (Tregs) subsets of SCD patients receiving regular blood transfusions with alloantibodies compared to those without, specifically a reduction in Treg activity, an increase toward T-helper cell type 2 (Th2) responses and lower serum levels of interleukin (IL) 10 in the alloimmunized group of patients. The same group (Bao et al, 2013) also presented data suggesting that regulatory B cells (Bregs) from alloimmunized and non-alloimmunized SCD patients differ in their ability to produce IL10 upon stimulation and dampen monocyte activation despite comparable frequencies of Bregs (CD19 + CD24 hi CD38 hi and CD24 hi CD27 + subsets) supporting an altered immunoregulatory state in alloimmunized SCD patients. Investigations of cytokine levels during acute SCD-related complications have shown increased neutrophil chemotaxis, monocyte phagocytosis and levels of IL6 and TNF during VOC (Graido-Gonzalez et al, 1998;Pathare et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…However, there is some evidence that Tregs in SCD display an altered phenotype and may have reduced immunosuppressive capacity, although the latter remains debated 46,47 . Of particular note, alloimmunization associated with frequent blood transfusion, a mainstay of treatment of SCD, may produce dysfunction in both Tregs 46 and regulatory B cells (Bregs) 48 . We and others have shown that Tregs 32,49,50 and Bregs 30,31,51 play important roles in the regulation of allergy and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T cells are known to suppress the activation and effector functions of many different cell types, in many different situations. The group of Yazdanbakhsh have explored this scenario with respect to RBC antigens in mice and humans, with the conclusion that certain phenotypes of regulatory T cells and B cells may influence responses to transfused RBC antigens [90,91,98,99]. Another group, however, failed to find functional differences in regulatory T cells in alloimmunized or non-alloimmunized humans with sickle cell disease [104].…”
Section: Recipient Factorsmentioning
confidence: 99%
“…However, there is much debate surrounding the reasons for the high rates of RBC alloimmunization [15,87,88], with potential factors including transfusion burden, RBC phenotypic differences between donors and recipients, and RBC genotypic variants in the sickle patients themselves. Sickle cell-associated vascular disease and chronic inflammation [89], as well as immune dysregulation [90,91], may also potentially contribute to the high rates of RBC alloimmunization in patients with sickle cell disease.…”
Section: Recipient Factorsmentioning
confidence: 99%